Creation of Polymer Coatings for Improving of Protective Properties of Surfaces (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, the preparation of polymer coatings on the surface of metal structural elements is considered to improve their physical, mechanical and strength properties. It is shown that the behavior of substrate samples under mechanical loads can be estimated using mathematical modeling methods. The properties of coatings and the mechanical properties of coated and uncoated metal plates have been evaluated. Methods for constructing mathematical models of metal plates of various structures are proposed.